Notes on Afrotropical Enicocephalidae and Reduviidae (Hemiptera: Heteroptera) with emphasis on vehicle-mounted net samples from Liberia, West Africa - Krüger, Andreas (Zootaxa, 2019)
Notes on the Enicocephalidae and Reduviidae (Hemiptera: Heteroptera) fauna in Liberia, sampled with various methods including a vehicle-mounted net, the species taxonomy and general distribution are presented, including 19 new country records. In addition, new country records are provided for Uganda, Togo, and Burkina Faso. Previously published Liberian records for 42 reduviids supplement the checklist.